Annealing improvement on the localized states of plasma grown boron nitride film assessed through admittance measurements - Ozdemir, Orhan; Anutgan, Mustafa; Aliyeva-Anutgan, Tamila; Atilgan, Ismail; Katircioglu, Bayram (ELSEVIER SCIENCE SA, 2009)
Boron nitride (BN) thin film was grown by plasma enhanced chemical vapor deposition (PECVD) technique and was investigated by UV-Visible transmission, Fourier transform infrared (FTIR) and ac conductance spectroscopies. Mainly the density of electronic localized states (D-it) at BN/Si interface was obtained by continuum and statistical models of ac conductance through an MIS structure (Al/BN film/Si). The origins of the electronic defects have been outlined and discussed within the frame of a nitrogen deficient turbostratic structure where more or less parallel hexagonal crystallites of distributed size would be embedded in a disordered phase. The nitrogen deficiency of the film was tried to be restored by annealing treatment under nitrogen atmosphere at two temperatures. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Turbostratic boron nitride; Admittance; DOS; Annealing; Dangling bond; Improvement; NEGATIVE ELECTRON-AFFINITY; EMISSION; DIAMOND; PECVD; BN; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering